Influence of carbon content on the primary solidification mode of high strength steels in resistance spot welding conditions. (15th July 2016) - Krajcarz, Florent; Gourgues-Lorenzon, A.-F.; Lucas, E.
Abstract: The primary solidification mode of resistance spot welds made of advanced high strength steels has been investigated as a function of carbon content. Electron backscatter diffraction and dendrite morphology analysis showed for the first time a transition from primary solidification into δ-ferrite (C ≤ 0.22 wt%) to primary solidification into austenite (C ≥ 0.29 wt%) with increasing carbon content. The description of this transition by using the so-called "interface response function" model is not fully satisfactory and strongly depends on input model parameters. Epitaxial growth from the heat-affected zone or from the slowly solidified zone could influence the solidification path. Graphical abstract: